Drumline - Stone III, Charles; Earl, Poitier; GQJason Weaver; Leonard Roberts; Orlando Jones; Zoe Saldana; Nick Cannon (USA Fox 2000 Pictures, 2002)
A fish-out-of-water comedy about a talented street drummer from Harlem who enrolls in a Southern university, expecting to lead its marching band's drumline to victory. He initially flounders in his new world, before realizing that it takes more than talent to reach the top.
A band director recruits a Harlem street drummer to play at a Southern university.
Shawn Schepps
Language(s): English
Subtitle(s): English, Turkish, Czech, Polish, Hungarian, Bulgarian, Hebrew, Icelandic, Romanian, Serbo-Croatian, Danish, Finnish, Norwegian, Russian
Keywords: Drama; Music; Romance; Comedy